Faktor-faktor yang Mempengaruhi Kualitas Penyajian Laporan Keuangan di Lingkungan Pemerintah Kota Padang Panjang - Popi Fauziati; Novaria Rahmah; Mukhlizul Hamdi (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2020)
This study aims to examine the effect of the adoption of Government Accounting Standards and Human Resource Competencies on the quality of the presentation of the Regional Financial Statements within the Government of Kota Padang Panjang, Sumatera Barat, Indonesia. The phenomenon is seen from the findings of the government auditors on the Padang Panjang Municipal Government Financial Report. In 2016 there were 14 findings that consisting of 8 findings on Compliance and 6 findings on Internal Control Systems, and in 2017 there were 11 findings consisting of 5 findings on Compliance and 6 findings on Internal Control Systems. As well as dealing with Human Resources Competence, there are still employees who are not / less competent, especially in the financial section in each organization. The sampling technique was purposive sampling, with 100 respondents, but only 50 respondents returned their questionnaires. Hypothesis testing using Multiple linear regression analysis with SPSS 16 application tools. The results showed that (1) the Application of Government Accounting Standards has a positive effect on the Quality of the Presentation of Government Financial Statements, (2) Human Resources Competence has a positive effect on the Quality of the Presentation of Government Financial StatementsKeywords: government accounting standards, human resources competence, quality of the financial statement ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh penerapan standar akuntansi pemerintah dan kompetensi sumberdaya manusia terhadap kualitas penyajian Laporan Keuangan Daerah di lingkungan Pemerintah Kota Padang Panjang. Fenomena penelitian ini didasarkan pada hasil pemeriksaan BPK-RI pada Tahun 2016 terdapat sejumlah 14 (empat belas)  temuan yang terdiri dari 8 (delapan) temuan tentang kepatuhan dan 6 (enam) temuan tentang sistem pengendalian internal. Pada tahun 2017 terdapat sejumlah 11 (sebelas)  temuan yang terdiri dari 5 (lima) temuan tentang kepatuhan dan 6 (enam) temuan tentang sistem pengendalian internal. Begitu juga dengan kompetensi Sumber Daya Manusia, masih ada karyawan yang tidak / kurang kompeten, terutama di bagian keuangan di organisasi pemerintah.Teknik pengambilan sampel adalah purposive sampling, dengan 100 responden, tetapi hanya 50 responden mengembalikan kuesioner.Pengujian hipotesis menggunakan analisis regresi linier berganda dengan menggunakan aplikasi SPSS 16.Hasil penelitian menunjukkan bahwa (1) penerapan standar akuntansi pemerintah memiliki pengaruh positif terhadap kualitas penyajian laporan keuangan pemerintah, (2) kompetensi sumberdaya manusia berpengaruh positif terhadap kualitas penyajian laporan keuangan pemerintah.Katakunci : standar akuntansi pemerintah, kompetensi sumberdaya manusia, kualitas penyajian laporan keuangan